2020
DOI: 10.1021/acschembio.9b00964
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Promiscuity of a Paralytic Shellfish Toxin Amidinotransferase

Abstract: Secondary metabolites are assembled by enzymes that often perform reactions with high selectivity and specificity. Many of these enzymes also tolerate variations in substrate structure, exhibiting promiscuity that enables various applications of a given biocatalyst. However, initial enzyme characterization studies frequently do not explore beyond the native substrates. This limited assessment of substrate scope contributes to the difficulty of identifying appropriate enzymes for specific synthetic applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Although the genes involved in sxt biosynthesis have been found in many cyanobacteria and dinoflagellates, there are few three-dimensional protein models. The crystallographic structure of an amidinotransferase annotated as sxtG in the cyanobacterium Microseira wollei has been recently published [ 83 ], highly different in amino acid number and sequence from the sxtG found in the present work. To our knowledge, these are the first in silico predictions of three-dimensional structures of sxt gene products in dinoflagellates.…”
Section: Resultsmentioning
confidence: 82%
“…Although the genes involved in sxt biosynthesis have been found in many cyanobacteria and dinoflagellates, there are few three-dimensional protein models. The crystallographic structure of an amidinotransferase annotated as sxtG in the cyanobacterium Microseira wollei has been recently published [ 83 ], highly different in amino acid number and sequence from the sxtG found in the present work. To our knowledge, these are the first in silico predictions of three-dimensional structures of sxt gene products in dinoflagellates.…”
Section: Resultsmentioning
confidence: 82%
“…Nine recent data sets from the literature were chosen toward this aim, for which both reactants and products were known (opposed to the more prevalent manner of only reporting reactants). Eight studies comprised enzymatic transformations, reporting the activity of different nitrilases, 45 aminedehydrogenases, 46 alcoholdehydrogenases, 47 carboxyl-methyltransferases, 48 transaminases, 49 tryptophansynthases, 50 amidinotransferases, 51 and dehalogenases 52 on diverse sets of substrates. An additional study on seven organic C(sp 2 )–C(sp 3 ) couplings 53 was utilized to showcase the performance of EHreact on nonenzymatic transformations.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For validation of the scoring function, a set of experimental studies on the substrate ranges of various enzymes was extracted from literature manually, [44][45][46][47][48][49][50][51] as well as a study on organic coupling reactions to test the performance of EHreact on organic, non-enzymatic reactions. 52 Each study reported either the yield or activity of an enzyme/catalyst on a specified substrate under reaction conditions consistent throughout each study.…”
Section: E Data Preparationmentioning
confidence: 99%